First Language Influence on Second Language Offline and Online Ambiguous Pronoun Resolution. Issue 3 (11th June 2018) - Schimke, Sarah; de la Fuente, Israel; Hemforth, Barbara; Colonna, Saveria
Abstract: This study examined first language (L1) influence on second language (L2) ambiguous pronoun resolution by investigating (a) whether L1 influence takes place at the level of the pronominal form (form‐dependent influence) and/or at the level of the construction in which the form appears (construction‐dependent influence) and (b) whether effects differ in online compared to offline data. In Experiment 1, we replicated previously observed construction‐dependent crosslinguistic differences between French and German and provided new data for Spanish. In Experiment 2, we assessed offline and online interpretation preferences of intermediate L1 French and L1 Spanish learners of German. Our results provide evidence of form‐dependent L1 influence, in that learners transferred a generalized antecedent bias associated with overt pronouns. Moreover, our results extend previous findings by showing that L1 influence on L2 pronoun resolution can occur during online processing. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the IRIS Repository athttps://www.iris-database.org/iris/app/home/detail?id=york:934337 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .